2004
DOI: 10.1007/s10336-004-0064-3
|View full text |Cite
|
Sign up to set email alerts
|

Two grouse clutches in the same nest: evidence for nest site adoption in capercaillie (Tetrao urogallus)

Abstract: We describe the case of an unusually large capercaillie Tetrao urogallus clutch consisting of 12 eggs, of which four chicks hatched. Eight eggs died in an early stage of development. Genetic analyses revealed that the putative mother of the chicks was different from the one laying the unhatched eggs. We compare our results with reports from clutches elsewhere and conclude that nest site adoption is a likely explanation for joint clutches in grouse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…However, this rarely seems to be a factor limiting clutch size in birds, particularly in Galliformes (Lack 1947, Skutch 1982), and such sex‐related differences in clutch size were not found in another study (Green 1984). Another explanation could be that several females lay eggs on the same nest, a behaviour relatively common in Galliformes (Filchagov 1996, Storch & Segelbacher 2005), including the Red‐legged Partridge (Casas et al. 2006b).…”
Section: Discussionmentioning
confidence: 99%
“…However, this rarely seems to be a factor limiting clutch size in birds, particularly in Galliformes (Lack 1947, Skutch 1982), and such sex‐related differences in clutch size were not found in another study (Green 1984). Another explanation could be that several females lay eggs on the same nest, a behaviour relatively common in Galliformes (Filchagov 1996, Storch & Segelbacher 2005), including the Red‐legged Partridge (Casas et al. 2006b).…”
Section: Discussionmentioning
confidence: 99%
“…Some research was conducted on Capercaillie incubation rhythm [20], but almost nothing is known about female-female interactions during nesting season. Despite the fact that such meetings may occur as suggested by Storch and Segelbacher [21] observations of clutches of two females in one nest. Authors based on nest analysis not witnessing the interactions themselves.…”
Section: Introductionmentioning
confidence: 93%
“…Clutch laying and incubation from multiple individuals is evident from various species [21,50]. Studies have shown that nest sharing is a more common behavior than expected and new reports are emerging for new bird species.…”
Section: Female/female Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…At that time, and also in those regions of the world, NGS started to be applied on birds, mainly due to the relative ease of locating samples in the field 16 as well as of obtaining DNA from shed feathers, 17 feces, or eggshells. 18 Subsequent advances in DNA isolation, purification, genotyping, and sequencing techniques based on low quantity and quality of genomic material—as non-invasive samples frequently yield—have allowed the expansion of NGS toward molecular ecology, population genetics, and conservation genetic studies. 13,19 For example, studies based on NGS of the capercaillie ( Tetrao urogallus ), an Eurasian galliform, have pioneered the use of feces and feathers as sources of genetic material.…”
Section: Introductionmentioning
confidence: 99%